Analysis of shear and degradation behaviour of fresh and fouled rail track ballast using large-scale direct shear tests - Venuja, S.; Navaratnarajah, S.K. (Institution of Engineers, Sri Lanka, 2021)
Railway transport plays a vital role in safely carrying away commuters and freights from one place to another, both short and long distances with comparatively low cost and high efficiency. Ballasted tracks and concrete slab tracks are widely utilized as railways for many countries. Substructure foundation of ballasted track system comprises a layered system with a ballast layer, followed by a capping layer and compacted subgrade over natural formation soil. The ballast layer is the major load-bearing layer that distributes loads from superstructure (wheel, rail and sleeper) to the underlying layers at a minimal level through a wider area. However, ballast undergoes deterioration with time under recurring cyclic and impact loadings due to less confinement. Accordingly, the service life span of rail track reduces as differential settlement and fouling resulted from ballast deterioration. Besides ballast is also contaminated with external fouling which obstructs the drainage of the layered foundation system. The shear stress and degradation behaviour of ballast with various fouling materials like sand and clay were analysed by conducting large-scale direct shear tests on fresh and fouled ballast with three different normal loads. The outcomes of this experimental study indicate that the compression, dilation and breakage behaviour of ballast depend on applied static normal load, type of fouling material and fouling percentage.
Keywords: Ballasted tracks; Layered system; Load-bearing; Degradation; Fouling